2014
DOI: 10.1007/s00062-013-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Image Features of the Atypical Teratoid/Rhabdoid Tumor in Adults: A Systematic Review

Abstract: We have experienced four adult-onset AT/RT cases at our institute and have evaluated image findings through systematic review. The image findings of high density on CT, high intensity on DWI, with low apparent diffusion coefficient, and a heterogenous component should lead to an inclusion of AT/RT in the differential diagnosis of a tumor; these findings may be able to suggest AT/RT; however, they cannot make the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
3
15
1
Order By: Relevance
“…Of note, our study and Torchia's series both focus on paediatric AT/RT, while a few AT/RT adult cases are reported 37 , challenging the proposed hypotheses of early embryonic progenitors as exclusive cells of origin. One explanation could be that a pool of embryonic neuron stem cells remains until adulthood.…”
Section: Discussioncontrasting
confidence: 60%
“…Of note, our study and Torchia's series both focus on paediatric AT/RT, while a few AT/RT adult cases are reported 37 , challenging the proposed hypotheses of early embryonic progenitors as exclusive cells of origin. One explanation could be that a pool of embryonic neuron stem cells remains until adulthood.…”
Section: Discussioncontrasting
confidence: 60%
“…Radiological findings from our case report were similar to those previously reported in adult AT/RT [5,9]. In our case, the tumour was hyperattenuated with cystic/necrotic components seen on CT.…”
Section: Discussionsupporting
confidence: 89%
“…In one case study, cerebral angiography showed tumour stain and early venous filling suggestive of a hypervascular tumour [9]. These radiological findings of a vascular tumour were consistent with our intraoperative findings.…”
Section: A C Bsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, the clinical manifestations and neuroimaging characteristics of patients often lacked specificity (19). Although mixed intensity in T2-weighted image, heterogeneous contrast enhancement, mild peritumoral edema, high density, and bone destruction on computed tomography have been reported frequently in adult-onset AT/RT (9,20), there are still great challenges in accurate diagnosis of AT/RT preoperatively. In clinical practice, AT/RT is easily misdiagnosed as other types of intracranial tumor before pathological confirmation.…”
Section: Discussionmentioning
confidence: 99%